2010
DOI: 10.3354/ame01356
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of symbiont-bearing dinoflagellates in the Indian Ocean in relation to oceanographic regimes

Abstract: The spatial distribution of symbiont-bearing dinoflagellates was investigated during a cruise from Cape Town, South Africa to Broome, Australia. Endo-and ectosymbionts were only found in the order Dinophysiales. The genera Ornithocercus, Histioneis, Parahistioneis and Citharistes had cyanobacteria as ectosymbionts, while the genera Amphisolenia and Triposolenia contained both intact cyanobacterial and eukaryotic endosymbionts. The symbiont-bearing dinoflagellates were mainly found in the upper 100 m of the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 30 publications
1
32
1
Order By: Relevance
“…Recently, we found that symbiont-bearing dinoflagellates were most common in the photic zone of the Indian Ocean characterized by low nutrients and low phytoplankton biomass (Tarangkoon et al 2010). This is consistent with previous observations from the Indian Ocean (Jyothibabu et al 2006) and the Red Sea (Gordon et al 1994).…”
Section: Introductionsupporting
confidence: 81%
“…Recently, we found that symbiont-bearing dinoflagellates were most common in the photic zone of the Indian Ocean characterized by low nutrients and low phytoplankton biomass (Tarangkoon et al 2010). This is consistent with previous observations from the Indian Ocean (Jyothibabu et al 2006) and the Red Sea (Gordon et al 1994).…”
Section: Introductionsupporting
confidence: 81%
“…Amphisolenia species, whilst known from surface water samples (e.g. Gó mez et al, 2011), are most abundant in sub-surface waters (100-200) but occur in down to 400 m depth (Tarangkoon et al, 2010). With regard to phaeogromid radiolarians, the species we denoted as common in the mesopelagic are also known from the mesopelagic of the Adriatic Sea (Kr sini c and Kr sini c, 2012) and the western and central Pacific Ocean (Yamashita et al, 2002).…”
mentioning
confidence: 99%
“…were also observed feeding on Myrionecta rubra by myzocytosis (Park et al 2006, Nishitani et al 2008. Very recently, Tarangkoon et al (2010) observed, with transmission electron microscopy, that Ornithocercus magnificus and Ornithocercus quadratus have a peduncle. Further, they observed that Ornithocercus spp.…”
Section: Feeding and Food Sourcementioning
confidence: 88%
“…are they true, permanent chloroplasts or kleptoplastids derived from chrysophyte or prymnesiophyte symbionts (Hallegraeff & Lucas 1988)? Aside from Clade B, the other 2 clades (A and C) are characterized by the presence of phycobilin-containing plastids or cyanobacterial endo-(or ecto-)symbionts, although eukaryotic endosymbionts within Amphisolenia and Triposolenia have also been observed (Tarangkoon et al 2010). Taylor (2004) thought that the phycobilin-containing dinophysoids Dinophysis, Amphisolenia and Triposolenia seemed more closely related to each other than to more morphologically complex (i.e.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation